HUBUNGAN PRESTASI AKADEMIK DENGAN KONSEP DIRI PADA MAHASISWA KEPERAWATAN SEMESTER V REGULER UNIVERSITAS SAM RATULANGI MANADO - Tangka, Ivana Belinda; Rottie, Julia; Bataha, Yolanda (Universitas Sam Ratulangi, 2018)
Abstract: The concept of self owned by a person will also determine how he receives, senses andresponds to his environment. Self-concept includes all self-perceptions of appearance, values, beliefsthat affect behavior. Students' success in achieving academic achievement will develop positive selfconcept.Aimed of research to determine whether there is a relationship of academic achievementwith self-concept in regular semester V nursing students of Sam Ratulangi University of Manado